Conventional sintering behavior of matrix materials used for diamond beads - Kahraman, Yusuf; Bulut, Berrak; Kayali, Eyup Sabri (CARL HANSER VERLAG, 2017)
Diamond tools are widely used in cutting process of natural stones. In the manufacturing process of diamond tools, matrix material can be sintered via different sintering methods such as spark plasma sintering (SPS), hot isostatic pressing (HIP) and conventional sintering (CS). CS method provides higher production capacity and lower cost when compared to other sintering methods, but mechanical properties are inferior to other sintering methods. Recent studies have the aim to obtain similar performance level as achieved by means of CS method. In this study, samples were prepared with three different compositions to be used for the CS method and characterized to evaluate their performance as a diamond bead matrix material. Experimental results showed that a study can be conducted to reach similar performances with Co matrix by using Ni matrix, and a high copper rate in matrix is undesirable since diamond tools are exposed to impact forces.
Keywords: Powder metallurgy; diamond tools; conventional sintering; materials performance; CUTTING TOOLS; CO; Materials Science